How audiences express emotions towards influencer short videos: Sentiment analysis of ‘my second uncle’ - Rongchun Xiao; Xiaoyu Guo; Xueying Xie (PLoS ONE, 2026)
As short videos dominate digital communication, this study examines audience emotional expression in this evolving media landscape. Focusing on the popular Chinese video “My Second Uncle”, we collected bullet subtitles—user comments displayed on-screen—and related comments. Using Latent Dirichlet Allocation (LDA), we identified key themes, while SnowNLP and ChatGPT facilitated an in-depth emotional analysis. Findings show a nuanced audience “gaze” toward the protagonist, with a strong trend of embracing his inspirational story, which generated predominantly positive emotional responses. Unlike traditional “gaze” research, engagement here was active and voluntary, with viewers using innovative online language. The study also reveals that influencer-driven short videos can quickly foster positive group sentiments, underscoring their potential for emotional healing and mental well-being.